FAMILY BEHAVIOR IN MALARIA PREVENTION IN BARUS SUBDISTRICT, CENTRAL TAPANULI REGENCY IN 2021 - Augustianny Situmeang; Tinawati Nainggolan; Putri Silitonga (Institute of Computer Science (IOCS), 2022)
Malaria is a life-threatening disease and has caused many deaths that are naturally transmitted through the bite of an infective anopheles betika mosquito. In 2016 North Sumatra Province was included in the 5th position with the number of cases of 3,807 cases /year while Central Tapanuli Regency occupied the 5th position of all regencies/cities in North Sumatra with a total of 314 cases. Malaria cases that have not been eliminated have resulted in a large number of cases that still occur every year. The living environment and habits of the surrounding community are important factors in the incidence of malaria in Central Tapanuli. This study aims to identify family behavior in malaria prevention in Barus District, Central Tapanuli Regency. The research design used was quantitative with a descriptive approach where the sample in this study was 97 families. The research instrument uses a questionnaire and then the data is processed using a computer system.